Analysis of variance in statistical image processing - Kurz Ludwik; Benteftifa M Hafed (Cambridge CUP, 1997)
This book provides an excellent text for understanding the nature and scope of sedimentation problems, methods for their investigation, and practical approaches to their solution. It focuses on sediment control methods for watersheds, streams, canals, an
Keywords: Analysis of variance; Applied statistics; Image processing-statistical methods